The functional actions of the rhetoric discourse (Eurasian Journal of Philology Science and Education, 2019)
The language function is a text function that is intertwined with other kinds of functions. Text is the basic unit of communication. People do not communicate with individual words, sentences but with texts. Though the concept of the word «text» is very old, but in the concept of terminology it appeared not so long ago.It is also logical that along with the concept of «text» the concept of «discourse» is widely used. In the field of linguistics, text and discourse are widely studied, but since this is a very large area of study, it requires careful study from various angles. Discourse is lika a language in a language. Discourse is a term that has many meanings, it is used in linguistic and psychological and historical research. The discourse acquires its full meaning only after people communicate with each other through conversation, in other words, it defines the meaning and unity, the unity of word and thought. Further development of discourse, the distinction of its types is possible only with the help of speech. They cannot be called holistic or complete. Currently, the discourse, which has received a scientific description, there are several types. One of them is the discourse of rhetoric.Since oratory is inherently special in nature, it can be the basis of linguistic parsing as a text. The article focuses on the functional activities of rhetorical discourse and specifies their main features.